Relationship Between Support for Workers With Illness and Work Functioning Impairment in Japan During the COVID-19 Pandemic. Issue 5 (25th May 2022) - Igarashi, Yu; Tateishi, Seiichiro; Harada, Arisa; Hino, Ayako; Tsuji, Mayumi; Ogami, Akira; Mori, Koji; Matsugaki, Ryutaro; Fujino, Yoshihisa
Abstract : This study revealed a relationship between support for workers with illness and work functioning impairment. While workers continue to work with illnesses has been increasing, this survey shows the importance for companies to support workers with illness. Abstract : Objective: This study examined the relationship between job accommodations for workers with poor health and work functioning impairment during the COVID-19 pandemic. Methods: An internet survey was conducted in December 2020. We included 24, 429 subjects for analysis. One question was used to determine whether subjects needed job accommodations from their company to continue working in their current health condition. The odds ratios (ORs) of the necessity of job accommodations for sick workers associated with work functioning impairment were estimated using multilevel logistic regression analysis. Results: The OR of work functioning impairment among sick workers not receiving job accommodations was 5.75 (95% confidence interval (CI): 5.34 to 6.20, P < 0.001) and those receiving job accommodations was 1.88 (95% CI: 1.69 to 2.08, P < 0.001) compared to healthy workers. Conclusions: This study suggests that providing job accommodations to workers with poor health may improve their work functioning impairment.